Identification of a functional cyclic adenosine 3',5'-monophosphate response element in the 5'-flanking region of the gene for transition protein 1 (TP1), a basic chromosomal protein of mammalian spermatids - Kistler, M K; Sassone-Corsi, P; Kistler, W S (Biology of reproduction, 1994)
Transition protein 1 (TP1) is a small basic chromosomal protein that appears in mammalian spermatids during the period of chromatin condensation. The gene for TP1 from several species contains an apparent cAMP response element (CRE) in the immediate 5'-flanking region. The recent identification of high expression of the novel CRE-activating protein (CREM tau) in advanced testicular germ cells provided a stimulus to ask whether or not the TP1 CRE is functional. To this end we show both by gel retardation and by footprint assays that TP1 CRE forms specific bound complexes with proteins in whole testis nuclear extracts and that these complexes involve CREM as evidenced by recognition by a specific antibody. In addition, the TP1 CRE forms specific bound complexes with bacterially expressed CREM tau. Finally, the TPI CRE conveys protein kinase A-dependent induction to a linked chloramphenicol acetyl transferase gene when transfected into JEG-3 cells. Accordingly, TP1 is a good candidate for a testis-specific gene subject to CREM tau regulation.